USING GAMES TO IMPROVE ENGLISH LANGUAGE TEACHING - Hamrayeva Durdona Farhod qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
In recent years, the use of games in English language teaching has gained significant attention as an effective pedagogical tool. Games create an engaging and motivating learning environment that encourages active participation and meaningful communication among learners. This article examines the role of games in improving English language teaching, focusing on their impact on learners’ motivation, language skills development, and classroom interaction. The study analyzes different types of games used in English language teaching and discusses their pedagogical benefits. The findings indicate that game-based learning enhances learners’ motivation, reduces anxiety, and improves overall language proficiency. The article also offers practical implications for English teachers.